Experimental study on Ahmed's body drag coefficient for different yaw angles. Issue 157 (October 2016) - Bello-Millán, F.J.; Mäkelä, T.; Parras, L.; del Pino, C.; Ferrera, C.
Abstract: We present experiments conducted in a wind tunnel to characterize yaw angle effects on the drag force acting on the Ahmed body with slant angle of 25°. The main contribution of this experimental work is to create a reliable database of drag coefficients under yawed conditions. For zero yaw angle, we find a small variation in the drag coefficient, C D, for Reynolds number in the range 3 × 10 5 − 30 × 10 5, resulting in the known tendency of a drag coefficient decrement as the Reynolds number increases. This trend is in agreement with other experimental works but is 30% greater than the usual C D ( Re ) function. Secondly, the drag coefficient increases significantly with an increment in the yaw angle at a constant Reynolds number. Three distinctive regions for the drag coefficient as a function of the yaw angles are established from the experimental results: the drag coefficient increases for 0 ° ≲ β ≲ 60 °, remains constant in the range 60 ° ≲ β ≲ 75 ° and finally, the drag coefficient grows again until β = 90 ° . Abstract : Highlights: We perform accurate experimental measurements of the drag coefficient on the Ahmed's body for different yaw angles. For null yaw angle, the results are far away from the usual trend, but they collapse with newer experimental results. Finally, we measure the drag force for different yaw angles showing different regions.